Projeto Oficina do Saber: sentidos do trabalho de professores na escola em tempo integral - Borges, Edmar José (2018)
The objective of this research was to investigate the meanings given by teachers of a full-time elementary public school of Sorocaba/SP to Project Oficina do Saber, focusing on the challenges and on the possibilities to the organization of their work. Specifically, the objectives were: a) to know the historical implementation context of Project Oficina do Saber in a public school of Sorocaba/SP; b) to understand the teacher’s work organizational context in the researched school; c) to know the concept of integral education for the teachers who work in Project Oficina do Saber and for its governing legal mechanism, the Orientations Report number 3. The theoretical and methodological principles that had been used were the historical-dialectical materialism and the historical-cultural theory. The methodological strategies that had been used were the documental analysis, participant observation with records in field camp and semi structured interviews conducted with three teachers. The results indicate that: a) Project Oficina do Saber’s historical implementation process in the researched school showed that a meaning of pedagogical complement has been given to the kid’s daily extend school time; b) The Orientations Report number 3 advocates an organizational mode for the pedagogical work wich is centered in the child and in its protagonism. However, this proposal is partly observed by the interviewed teachers, due to factors such as lack of resources, absence of administrative and pedagogical support and working requirements that are beyond the teacher’s formation possibilities; c) the Report number 3 conceives integral education as integrated child formation, considering all of his or her dimensions: cognitive, affective, ethical, social, playful, esthetic, physical and biological; the teachers conceive the integral education as a way of preparing children for life in society, both for the acquisition of cognitive or emotional competences. Project Oficina do Saber’s proposal and the pedagogical work that have been developed are considered to be articulated to the interests of dominant classes, strengthening the fundamentals of the neoliberal capitalist production mode and precluding the implementation of integral education as human formation in the Marxist perspective; in this sense, conceiving ways of articulating integral education in full-time school to the interests of working class is considered necessary.